Pattern recognition applications and methods : International Conference, ICPRAM 2014, Angers, France, March 6-8, 2014, Revised selected papers /: International Conference, ICPRAM 2014, Angers, France, March 6-8, 2014, Revised selected papers. (2015) - Unknown
No abstract available